Reconsidering the Role of Sleep Hygiene in Sleep: How are Sleep Hygiene Behaviours Really Impacting our Sleep? - McAlpine, Thomas (Curtin University, 2023)
The overarching aim of this thesis was to assess the association between a broad range of sleep hygiene behaviours and sleep for non-clinical populations. A mixture of cross-sectional correlational and repeated measures designs across four studies demonstrated that consideration of the sleep parameter in which each sleep hygiene behaviour is associated with sleep may be critical for future work looking to optimise sleep in the general population.